2016
DOI: 10.1149/2.01111701jes
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed Water on Nano-Silicon Powder and Its Effects on Charge and Discharge Characteristics as Anode in Lithium-Ion Batteries

Abstract: The amounts of adsorbed water on several kinds of carbon and silicon materials including Si nano-flake powder (Si LeafPowder, Si-LP) were determined at 250 • C. It was found that nano-sized Si materials adsorb a large amount of water even after being dried at 120 • C because of the hydrophilicity of the surface and the high specific surface area. The adsorbed water on Si-LP can be removed, but not completely, after drying at a 180 • C. The charge and discharge characteristics of Si-LP, especially the initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…While the bulk oxidation mediates the overall capacity of the Si material, as seen by the changes in specific capacity (Figure 9), the surface chemistry plays an important role in binder interactions, 24−26 SEI formation, 27−29 and the adsorption of water to the Si surface. 30 The surface of the unprocessed NA 70−130 Si particles was identified to contain a mix of Si− H, geminal, silanol, and siloxane sites. The NMP had minimal effect on these surface species, but after water processing, the Si−H, geminal, and siloxane sites were largely converted to silanol groups, which is common among a fully hydrated silica surface.…”
Section: ■ Discussionmentioning
confidence: 99%
“…While the bulk oxidation mediates the overall capacity of the Si material, as seen by the changes in specific capacity (Figure 9), the surface chemistry plays an important role in binder interactions, 24−26 SEI formation, 27−29 and the adsorption of water to the Si surface. 30 The surface of the unprocessed NA 70−130 Si particles was identified to contain a mix of Si− H, geminal, silanol, and siloxane sites. The NMP had minimal effect on these surface species, but after water processing, the Si−H, geminal, and siloxane sites were largely converted to silanol groups, which is common among a fully hydrated silica surface.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35]. Such processing exposes the materials to moisture, resulting in numerous complications [36][37][38] associated with the hydrolysis of lithium salts [39][40][41][42][43] and of the carbonate solvents. 44,45 Introduction of moisture, and electrochemical or chemical generation of corrosive acids near the positive electrodes, are a particular concern for oxide materials cycled at voltages >4.5 V vs Li/Li + .…”
Section: LImentioning
confidence: 99%
“…We reported that a higher drying temperature of 180°C gives higher coulombic efficiencies for Si-LP anode. 36 It should be noted that the amount of adsorbed water is approximately proportional to the specific surface area of Si materials in Fig. 9.…”
Section: Ceaseless Electrolyte Decomposition and Sei Growthmentioning
confidence: 88%
“…36 Figure 9 shows the relationships between the content of adsorbed water and BET specific surface areas of various Si and carbon powder materials. 36 Here the samples were dried at 120°C for 1 h in N 2 , and the adsorbed water was measured by heating the samples at 250°C in N 2 . Generally graphite and Si anodes were dried at 100-120°C under vacuum before assembling the cells.…”
Section: Ceaseless Electrolyte Decomposition and Sei Growthmentioning
confidence: 99%
See 1 more Smart Citation